The importance of professional ethics in the work action of Brazilian interior designers - Pires Corrêa, Maira; Rezende, Edson José Carpintero (DAT Journal, 2025)
Respecting ethical standards and values is a significant factor for professional consolidation. With that said, this article is the result of a descriptive research. Using the snowball sampling technique, 10 interior designers who work in the Belo Horizonte and the metropolitan region market were interviewed. The objective was to collect information about important ethical principles in professional practice. For this purpose, data were obtained through bibliographic references, codes of professional conduct, Brazilian legislation, as well as one interview form. It was observed that is necessary for interior designers to take a closer look at the code of ethics suggested by ABD in the country, as well as the sections of Law 13.369/2016. However, each designer must question themselves regarding the relevance of their actions and project choices, because it affect directly the exercise of the activity.